Grain refinement of Fe--Ti alloys fabricated by laser powder bed fusion. (June 2021) - Ikehata, Hideaki; Mayweg, David; Jägle, Eric
Abstract: Grain structure control is essential in metal additive manufacturing. It is used to avoid anisotropic mechanical properties, hot cracking and to increase the strength via the Hall-Petch effect. Here we demonstrate the use of grain refining particles for grain control in ferritic alloys, specifically Fe-Ti model alloys. We introduce the particles in three different ways, namely (i) by using oxygen-rich raw powders, (ii) by reaction of the molten material with the process gas atmosphere and (iii) by direct addition of the refining ceramic phase in powder form. Samples are produced by Laser Powder Bed Fusion with various concentrations of Ti and under Ar and N2 atmosphere. The resulting microstructures are analyzed using optical and electron microscopy. We demonstrate a transition from a microstructure containing columnar grains >100 μm in length to a strongly grain refined microstructure with equiaxed grains of approx. 1 μm in size. The refining sub-micron-sized particles in all cases are cubic Ti(O, N). We discuss the findings in the light of thermodynamic calculations as well as established grain refinement models. Graphical abstract: Unlabelled Image Highlights: Samples of Fe-Ti model alloys were produced by Laser Powder Bed Fusion under Ar and N2 atmosphere. A transition from a microstructure containing coarse columnar grains to a refined microstructure with equiaxed grains was confirmed. Cubic Ti(O, N) particles with the Baker-Nutting orientation relationship realize grain refinement by heterogeneous nucleation.